Dyslipidemia is Associated with Unfit and Overweight-Obese Children and Adolescents - Reuter,Cézane Priscila (2016)
Abstract Background: Both poor aerobic fitness and obesity, separately, are associated with abnormal lipid profiles. Objective: To identify possible relationships of dyslipidemia with cardiorespiratory fitness and obesity, evaluated together, in children and adolescents. Methods: This cross-sectional study included 1,243 children and adolescents (563 males and 680 females) between 7 and 17 years of age from 19 schools. Obesity was assessed using body mass index (BMI) measurements, and cardiorespiratory fitness was determined via a 9-minute run/walk test. To analyze the lipid profile of each subject, the following markers were used: total cholesterol, cholesterol fractions (high-density lipoprotein and low-density lipoprotein) and triglycerides. Data were analyzed using SPSS v. 20.0, via prevalence ratio (PR), using the Poisson regression. Results: Dyslipidemia is more prevalent among unfit/overweight-obese children and adolescents compared with fit/underweight-normal weight boys (PR: 1.25; p = 0.007) and girls (PR: 1.30, p = 0.001). Conclusions: The prevalence of dyslipidemia is directly related to both obesity and lower levels of cardiorespiratory fitness.